Constitutional and Normative Position of Belgrade as an Obstacle in the Exercise of Local Democracy - Jerinić, Jelena (Serbian political thought, 2023)
During the last few decades, the reluctance to take significant steps in the reform of the territorial organization and local self-government system in Serbia had an adverse effect on both small and underdeveloped, as well as large and economically advanced municipalities and towns. In this paper, the author's intention is to show that the constitutional and legal position of the City of Belgrade, within the framework of a single-level and uniform system of local self-government, among other issues, prevents the implementation of various mechanisms of local democracy, regulated by Serbian laws. Trapped in such a system, Belgrade and its authorities remain completely distant from citizens. The inadequacy of formal mechanisms of local democracy which are incorporated into the legal solutions on the system of local self-government is primarily shown here on the example of the organization of city municipalities, which during the last twenty years have been completely devoid of self-governing characteristics, as well as the specific form of optionality in the establishment of local community units (mesne zajednice) at the level of the capital city. Solutions could be sought in comprehensive changes to the territorial organization and the system of local self-government, which, apparently, require changes to the Constitution, and which would enable the capital city to (at least) have the position of the second tier of local self-government. Belgrade's fitness to be more than a first-level unit of local self-government can be confirmed by a simple analysis of the tasks delegated to the City in certain areas, in which it already has the position of a second-tier administrative authority.